2013
DOI: 10.11114/jets.v1i2.152
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Teacher’s Perceptions of the Role of Social Studies in Fostering Citizenship Competencies

Abstract: This study investigated the perceptions of the role of Botswana's social studies teachers at secondary school level in fostering citizenship competencies and skills. Survey questionnaires were used to collect data comprising close and open-ended questions. The total population comprised forty-one respondents purposively sampled from nine junior and senior secondary schools in rural and urban locations. These included thirty four social studies teachers and seven head of departments. Data were analyzed quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Many of the participants in their study conceptualized social studies as a subject aiming to develop their history, geography, and citizenship related skills. Boikhutso, Dinama, and Kgotlaetsile (2013) examined how social studies teachers perceived the role of social studies curriculum in developing secondary school students' citizenship competences in Bostwana. The results indicated that the participants thought that the social studies curriculum did not play the foreseen role of developing students' citizenship competences.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Many of the participants in their study conceptualized social studies as a subject aiming to develop their history, geography, and citizenship related skills. Boikhutso, Dinama, and Kgotlaetsile (2013) examined how social studies teachers perceived the role of social studies curriculum in developing secondary school students' citizenship competences in Bostwana. The results indicated that the participants thought that the social studies curriculum did not play the foreseen role of developing students' citizenship competences.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…The government of Botswana introduced Social Studies at both primary and junior secondary school curricular in 1982 (Boikhutso et al, 2013). The reason being that the people of Botswana had a general conviction that their education system was not relevant to the citizenry because it was colonially oriented (Boikhutso, 1993) in Boikhutso et al (2013).…”
Section: Botswanamentioning
confidence: 99%
“…The government of Botswana introduced Social Studies at both primary and junior secondary school curricular in 1982 (Boikhutso et al, 2013). The reason being that the people of Botswana had a general conviction that their education system was not relevant to the citizenry because it was colonially oriented (Boikhutso, 1993) in Boikhutso et al (2013). This meant that the education curriculum did not inculcate relevant competences which would develop the citizens in a holistic manner but make them more submissive to the commands and expectations of the white minority.…”
Section: Botswanamentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 43 objectives stated in the lesson plans, only 21 (48.8%) had proper integration while 22 (51.2%) did not have proper integration. In response to this shortcoming, Boikhutso et al (2013) give an important advice that successful implementation of moral education requires social studies teachers who are well trained and competent to contextualize moral value aspects in the teaching-learning transaction and in that way handle educational reforms. This suggests that teachers of social sciences need to be acquainted with specific approaches that will enable them to contextualize facts into practical application in learners' day-to-day life.…”
Section: Teachers' Descriptive Statistics On Integration Of Moral Valuesmentioning
confidence: 99%